Comparative Genome-Wide Analysis Underscores the Rapid Expansion of Cytochrome P450s for Secondary Metabolism in the Mycoparasite Pezizomycetes - Puleng Rosinah Syed; Tiara Padayachee; Philasande Gamede; Bridget Valeria Zinhle Nkosi; David R. Nelson; Rajshekhar Karpoormath; Khajamohiddin Syed (Microbiology Research, 2024)
Mycoparasite secondary metabolites control fungal infections or diseases in agriculture and human health. Among genes involved in synthesizing secondary metabolites, cytochrome P450 monooxygenases (CYPs/P450s) play a key role in synthesizing and attributing diversity to the secondary metabolites. Despite the importance of P450s, a comparative analysis of P450s in mycoparasites has yet to be reported. This study is aimed at addressing this research gap. Genome-wide analysis of P450s in 43 fungi representing six fungal phyla and three distinct lifestyles, such as mycoparasitic (24 species), saprophytic (5 species), and ectomycorrhizal (14 species), revealed the expansion of P450s in Pezizomycete mycoparasites for the synthesis of secondary metabolites. The number of P450s and their families and subfamilies, the number of secondary-metabolite biosynthetic gene clusters (SMBGCs), and the number of P450s that are part of these SMBGCs were found to be highest in Pezizomycete mycoparasites compared to their counterparts of saprophytes and ectomycorrhiza, indicating P450s also play a key role in mycoparasitism. An analysis of P450 location as part of SMBGCs and the available literature on Pezizomycete P450s revealed that P450s play a key role in the synthesis of anti-fungal secondary metabolites such as trichothecene sesquiterpene, harzianum A, heptelidic acid, and gliotoxin. The mycoparasite Trichoderma virens Tv29.8 P450 CYP68Q3 is found to be a bifunctional enzyme with epoxidation and oxidation capability, and CYP5117A3 performs a Baeyer–Villiger oxidation reaction with regioselectivity. This study serves as a reference for future annotation of P450s in mycoparasites.